Positive Patch-Test Reactions to Essential Oils in Consecutive Patients From North America and Central Europe. Issue 4 (July 2017) - Warshaw, Erin M.; Zug, Kathryn A.; Belsito, Donald V.; Fowler, Joseph F.; DeKoven, Joel G.; Sasseville, Denis; Maibach, Howard I.; Mathias, C.G. Toby; DeLeo, Vincent A.; Taylor, James S.; Fransway, Anthony F.; Marks, James G.; et al.
Abstract : Background: Synthetic fragrances and natural essential oils (EOs) are used in perfumery and found in various cosmetics. Essential oils are also increasingly used to promote wellness. In previous studies, the sensitization potential of some EOs has been identified; however, the current prevalence of sensitivity is largely unknown. Objectives: The aim of this study was to determine frequency of positive patch-test reactions to EOs tested in the baseline series, along with 3 fragrance markers (FMs) (fragrance mix I, fragrance mix II, and Myroxylon pereirae ), in consecutive patients in the US/Canadian North American Contact Dermatitis Group (NACDG) (2009–2014) and the central European, trinational Information Network of Departments of Dermatology (IVDK) (2010–2014). Methods: This study used a retrospective analysis of patch-test results and relevant demographic/clinical data collected electronically by the networks, obtained with Santalum album 10% petrolatum (pet) (IVDK only); Cananga odorata 2% (NACDG) and 10% (IVDK) pet; Jasminum species 2% (NACDG) and 5% (IVDK) pet; Mentha piperita 2% pet; Melaleuca alternifolia, oxidized (tea tree oil), 5% pet; and Lavandula angustifolia 2% pet (latter 3 NACDG only). Results: Overall, 62, 354 patients were tested to 3 FMs and EOs (NACDG, 13, 398; IVDK, 48, 956); 11, 568 (18.6%) reacted to at least 1 FM or EO, whereas 857 (1.4%) reacted to 1 or more EOs but none of the 3 FMs. For both the NACDG and IVDK populations, individuals who were positive to 1 or more of the 9 study allergens were significantly less likely to be male, have occupational skin disease, or have hand involvement and significantly more likely to have leg dermatitis and be 40 years and older ( P 's ⩽ 0.005). Prevalence rates for EOs were as follows: S. album, 1.4% IVDK; C. odorata, 1.1% NACDG and 2.4% IVDK; Jasminum species, 0.7% NACDG and 1.4% IVDK; M. piperita, 0.9% NACDG; L. angustifolia, 0.3% NACDG; and M. alternifolia, 0.3% NACDG. Of the 140 NACDG patients who reacted to 1 or more of the 5 NACDG EOs but none of the FMs, M. alternifolia yielded most positive reactions (45%); half of these reactions were strong (++ or +++, 50.8%) and of definite/probable clinical relevance (52.4%). Of the 717 IVDK patients who reacted to 1 or more of the 3 IVDK EOs but none of the 3 FMs, 38% were positive to C. odorata, 38% to S. album and 36% to Jasminum species ." Conclusions: Testing to EOs may be important for detecting sensitivity not detected by FMs alone. In North America, M. alternifolia is an important and clinically relevant sensitizer often not detected by FM. In Europe, as well as in North America, clinical relevance is often difficult to evaluate because (1) labeling of EOs when used as fragrance is not mandatory, and (2) these mixtures may indicate sensitization to 1 or more of their individual constituents from other sources, including synthetic fragrances.